Coccygeal vertebra as an alternative to traditional autograft bone - tomography and biomechanical study in ex vivo dogs - Serafini, Gabriele Maria Callegaro; Pippi, Ney Luis; Libardoni, Roberta do Nascimento; Libardoni, Renato do Nascimento; Müller, Daniel Curvello de Mendonça; Amaral, Bruna Portolan; Zanella, Igor Giacomelli; Cauduro, Carlos Roberto (Brazilian Journal of Veterinary Medicine, 2018)
Bone grafting is a resource widely used by the veterinary orthopedic surgeon for reconstruction of affected limbs for a total loss of a cortical bone segment. However, the absence of bone bank and the presence of autografts with insufficient structural dimensions are feared setbacks in choosing this resource. Because of this, this study aimed to investigate the structural characteristics of coccygeal vertebra suggesting it as a possible alternative to bone autograft. For this, were used eight, ex vivos, dogs, with each dog donor of two samples of each bone grafts following groups: cranial-dorsal portion of the right and left iliac crest (group A), 10th fragment of the right and left ribs (group C), 4th and 5th coccygeal vertebrae (group Co) and diaphyseal portion of the right and left tibia (group T), resulting in 16 samples per group. Such grafts underwent computed tomography for measurement of cancellous bone and cortical bone and biomechanical test to evaluate the resistance. The coccygeal vertebra offered good bone strength and showed a high percentage of cancellous bone, conferring to it, in addition to probable large power osteogenic also structural support